MATHPRO 4.0 / Norlida Othman - Othman, Norlida (Universiti Teknologi MARA, Negeri Sembilan, 2022)
PROGRAM REVIEW - MATHPRO is a periodic program, regularly organized by Cybermath Club that aims to stretch mathematical thinking and improve teamwork skills among UiTM Kuala Pilah students. This is the 4th time MATHPRO has been implemented and received positive feedback from the participants. This program's goal is to pique the curiosity of UiTM Kuala Pilah students about learning mathematics through various instructional strategies. Additionally, it offers a variety of tools and activities to enhance student's skills to handle obstacles and answer problems quickly, which can assist the Mathematics department in determining what improvements can be done. The platforms used for this program were Google Meet and Cisco Webex on June 10, 2022. This program was attended by 80 students who are currently taking MAT133, MAT183 and MAT122.